Status of implementation of short answer question in anatomy examination of MBBS course in Bangladesh - Akhter, Jesmin; Sayeed, Sharmina (IMC Journal of Medical Science, 2019)
Background and objective: Short answer question (SAQ) format has been introduced as a major component of summative professional examinations of MBBS (Bachelor of Medicine and Surgery) course in Bangladesh over a decade. No systematic evaluation has yet been conducted on implementation of SAQ as directed in curriculum to assess the medical students in the summative examination of MBBS course. The present study assessed the weightage given to the different components of cognitive domain in SAQs in anatomy in first Professional MBBS Examination under the University of Dhaka. Materials and method: This cross-sectional study was conducted in the Department of Anatomy, Ibrahim Medical College. Anatomy SAQ papers, Paper I and Paper II, from January 2009 to July 2014 of University of Dhaka were selected. A total of 24 SAQ papers containing 572 questions were included in this study. Every question in a paper was categorized as recall, understanding application types. Then the total number of marks allocated for each of the type of questions were calculated and compared with the total marks (98) allocated for the questions in a paper. Then the resultant weightage of marks were compared with the curricular directive weightage of marks allotted for SAQ. Result: On analysis it was found that during the period from 2009 to 2014 76.58% and 23.42% SAQ were recall and understanding types respectively. No question was found to assess the application component of the cognitive domain of the students. Conclusion: The study revealed that SAQ introduced as an assessment tool in undergraduate medical curriculum was not properly implemented and its desired objectives were not fully achieved. IMC J Med Sci 2018; 12(2): 69-72